Criminal Liability Policy for Organizers of the Free Nutritious Meal Program in Mass Food Poisoning Cases: A Legal Certainty Approach - Suryana, Dian; Dini Dewi Heniarti (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
The free nutritious meal program is a national public service policy intended to strengthen nutritional fulfillment for vulnerable groups; however, its large-scale food distribution system also creates serious food safety risks, including the possibility of mass poisoning incidents. This study examines the normative problem of unclear criminal accountability in free nutritious meal governance, particularly the absence of a foreseeable accountability map that distinguishes administrative violations from criminal conduct and identifies the relevant legal subjects. The research addresses two questions about how criminal liability is constructed in food safety incidents within the free nutritious meal program, and how the chain of criminal responsibility among the government, the National Nutrition Agency, schools, and vendors should be structured within a public policy framework. This study employs doctrinal legal research using statutory, conceptual, and comparative approaches through the examination of criminal law, food law, consumer protection law, and selected comparative references from Japan, India, and China. The findings show that Indonesian positive law provides a fragmented basis for liability through negligence offenses in the Criminal Code and criminal provisions in food and consumer legislation, yet these norms remain insufficient for a multi-actor public policy program such as the free nutritious meal. This condition creates uncertainty in liability attribution and risks selective criminalization or structural impunity. The study concludes that the free nutritious meal requires a statutory lex specialis that clearly regulates minimum food safety standards, liable legal subjects, fault thresholds, causation standards, and tiered sanctions in order to ensure legal certainty and effective public protection.